2020
DOI: 10.1099/ijsem.0.004511
|View full text |Cite
|
Sign up to set email alerts
|

Novel acetic acid bacteria from cider fermentations: Acetobacter conturbans sp. nov. and Acetobacter fallax sp. nov

Abstract: Strains LMG 1627T, LMG 1636T and LMG 1637 were all isolated from cider fermentations in the 1940s and 1950s. A recent study based on MALDI-TOF MS and dnaK gene sequence analyses suggested they represented novel Acetobacter species. In the present study, we determined the whole-genome sequences of these strains and analysed their phenotypic and chemotaxonomic characteristics. A phylogenomic analysis based on 107 single-copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, strains SYSU D00823 T , SYSU D00873 T and P. xinjiangensis CCTCC AB 208092 T showed 56.7-57.3 % POCP values with P. mongoliensis KCTC 52859 T . Although a 50 % POCP cut-off value was proposed for defining bacterial genera [23], it has been shown that this universal cut-off is too conservative to be appropriate for circumscribing many bacterial genera [31][32][33]. The detailed paired overall genome relatedness indices (OGRIs) are shown in Table 2.…”
Section: Genome Featuresmentioning
confidence: 99%
“…Furthermore, strains SYSU D00823 T , SYSU D00873 T and P. xinjiangensis CCTCC AB 208092 T showed 56.7-57.3 % POCP values with P. mongoliensis KCTC 52859 T . Although a 50 % POCP cut-off value was proposed for defining bacterial genera [23], it has been shown that this universal cut-off is too conservative to be appropriate for circumscribing many bacterial genera [31][32][33]. The detailed paired overall genome relatedness indices (OGRIs) are shown in Table 2.…”
Section: Genome Featuresmentioning
confidence: 99%
“…Researchers have striving to isolate high-performing acetic acid bacteria from vinegar grains, vinegar mash, and decay sites of fruits. Recently, Acetobacter pasteurianus ( Wu et al, 2018 ), Acetobacter aceti ( Sombolestani et al, 2020 ), Acetobacter rancens ( Zheng, Liu, Zhang, & Wang, 2010 ), and Acetobacter malorum ( Sainz, Mas, & Torija, 2017 ) stand out as the most frequently employed strains in fruit vinegar fermentation. These Acetobacter strains demonstrated the ability to convert alcohol into acetic acid, meanwhile, some volatile aroma components such as organic acids, esters, ketones, and aldehydes were produced, giving fruit vinegar complex aroma and flavor.…”
Section: Strains Used For Fruit Fermentationmentioning
confidence: 99%
“…To test ketogenesis from glycerol, isolates were cultivated on agar medium containing 2.5 % (w/v) agar and 2 % (w/v) glycerol at 28 °C for 2 h under aerobic conditions. The cultures were then covered with Benedict reagent (17.3 % (w/v) sodium citrate, 10 % (w/v) sodium carbonate, 1.73 % (w/v) copper sulphate pentahydrate) and incubated under the same conditions for another 3 h [57]. The presence of 2-keto- d -gluconic acid and 5-keto- d -gluconic acid was determined in triplicate by HPLC using a Prominence-i separation module (Shimadzu) equipped with an HPX-87H column (Bio-Rad) and a photodiode array detector (Shimadzu).…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%